Diverging patterns of plasticity in the nucleus basalis of Meynert in early- and late-onset blindness. Issue 2 (11th April 2023) - Bang, Ji Won; Chan, Russell W; Parra, Carlos; Murphy, Matthew C; Schuman, Joel S; Nau, Amy C; Chan, Kevin C
Abstract: Plasticity in the brain is impacted by an individual's age at the onset of the blindness. However, what drives the varying degrees of plasticity remains largely unclear. One possible explanation attributes the mechanisms for the differing levels of plasticity to the cholinergic signals originating in the nucleus basalis of Meynert. This explanation is based on the fact that the nucleus basalis of Meynert can modulate cortical processes such as plasticity and sensory encoding through its widespread cholinergic projections. Nevertheless, there is no direct evidence indicating that the nucleus basalis of Meynert undergoes plastic changes following blindness. Therefore, using multiparametric magnetic resonance imaging, we examined if the structural and functional properties of the nucleus basalis of Meynert differ between early blind, late blind and sighted individuals. We observed that early and late blind individuals had a preserved volumetric size and cerebrovascular reactivity in the nucleus basalis of Meynert. However, we observed a reduction in the directionality of water diffusion in both early and late blind individuals compared to sighted individuals. Notably, the nucleus basalis of Meynert presented diverging patterns of functional connectivity between early and late blind individuals. This functional connectivity was enhanced at both global and local (visual, language and default-mode networks) levels in the early blind individuals, but there were little-to-no changes in the late blind individuals when compared to sighted controls. Furthermore, the age at onset of blindness predicted both global and local functional connectivity. These results suggest that upon reduced directionality of water diffusion in the nucleus basalis of Meynert, cholinergic influence may be stronger for the early blind compared to the late blind individuals. Our findings are important to unravelling why early blind individuals present stronger and more widespread cross-modal plasticity compared to late blind individuals. Abstract : Bang et al . reported that the nucleus basalis of Meynert, the major source of cholinergic signals, presents diverging patterns of plasticity across early- and late-onset blindness. While its directionality of water diffusion is reduced in both early- and late-onset blindness, its functional connectivity is increased only in early blind individuals. Graphical Abstract: Graphical Abstract